Benthic Nitrogen Loss in the Arabian Sea Off Pakistan - Sokoll, Sarah; Holtappels, Moritz; Lam, Phyllis; Collins, Gavin; Schlüter, Michael; Lavik, Gaute; Kuypers, Marcel M. (Frontiers in Microbiology, 2012)
A pronounced deficit of nitrogen (N) in the oxygen minimum zone (OMZ) of the Arabian Sea suggests the occurrence of heavy N-loss that is commonly attributed to pelagic processes. However, the OMZ water is in direct contact with sediments on three sides of the basin. Contribution from benthic N-loss to the total N-loss in the Arabian Sea remains largely unassessed. In October 2007, we sampled the water column and surface sediments along a transect cross-cutting the Arabian Sea OMZ at the Pakistan continental margin, covering a range of station depths from 360 to 1430 m. Benthic denitrification and anammox rates were determined by using 15N-stable isotope pairing experiments. Intact core incubations showed declining rates of total benthic N-loss with water depth from 0.55 to 0.18 mmol N m-2 d-1. While denitrification rates measured in slurry incubations decreased from 2.73 to 1.46 mmol N m-2 d-1 with water depth, anammox rates increased from 0.21 to 0.89 mmol N m-2 d-1. Hence, the contribution from anammox to total benthic N-loss increased from 7% at 360 m to 40% at 1430 m. This trend is further supported by the quantification of nirS, the biomarker functional gene encoding for cytochrome cd1-nitrite reductases of microorganisms involved in both N-loss processes. Anammox-like nirS genes within the sediments increased in proportion to total nirS gene copies with water depth. Moreover, phylogenetic analyses of nirS revealed different communities of both denitrifying and anammox bacteria between shallow and deep stations. Together, rate measurement and nirS analyses showed that anammox, determined for the first time in the Arabian Sea sediments, is an important benthic N-loss process at the continental margin off Pakistan, especially in the sediments at deeper water depths. Extrapolation from the measured benthic N-loss to all shelf sediments within the basin suggests that benthic N-loss may be responsible for about half of the overall N-loss in the Arabian Sea.